Influence of the Intensive Care Unit Environment on the Reliability of the Montreal Cognitive Assessment - Stienen, Martin Nikolaus; Geisseler, Olivia; Velz, Julia; Maldaner, Nicolai; Sebök, Martina; Dannecker, Noemi; Rothacher, Yannick; Schlosser, Ladina; Smoll, Nicolas Roydon; Keller, Emanuela; Brugger, Peter; Regli, Luca (Frontiers in Neurology, 2019)
Background: Neuropsychological screening becomes increasingly important for the evaluation of subarachnoid hemorrhage (SAH) and stroke patients. It is often performed during the surveillance period on the intensive (ICU) already, while it remains unknown, whether the distraction in this environment influences the results. We aimed to study the reliability of the Montreal Cognitive Assessment (MoCA) in the ICU environment. Methods: Consecutive stable acute brain injury patients were evaluated twice within 36 hours using official parallel versions of the MoCA (ΔMoCA). The sequence of assessment was randomized into a) busy ICU first or b) quiet office first with subsequent crossover. For repeated MoCA, we determined sequence, period, location effects, and the intraclass correlation coefficient (ICC). Results: N=50 patients were studied (n=30 (60%) male), with a mean age of 57 years (standard deviation (SD) 17.2). The assessment’s sequence (“ICU first” mean ΔMoCA -1.14 (SD 2.34) vs. “Office first” -0.73 (SD 1.52)) did not influence the MoCA (p=0.47). On the 2nd period, participants scored 0.96 points worse (SD 2.01; p=0.001), indicating no MoCA learning effect but a possible difference in parallel versions. There was no location effect (p=0.31) with ΔMoCA between locations (Office minus ICU) of -0.32 (SD 2.21). The ICC for repeated MoCA was 0.87 (95% CI 0.79 – 0.92). Conclusions: The reliability of the MoCA was excellent, independent from the testing environment being ICU or office. This finding is helpful for patient care and studies investigating the effect of therapeutic interventions on the neuropsychological outcome after SAH, stroke or traumatic brain injury.